Bank loan or financing for weddings ceremonies: causes and reasons - Fatimah Salwa Abd. Hadi (Tanjong Malim, 2019)
Bank loan or financing for weddings ceremonies: causes and reasons by Fatimah Salwa Abd. Hadi